Transition metal sulfide heterojunction with wide spectral response and preparation method and application thereof

WOx/ZnIn2S4 heterojunction was synthesized through hydrothermal-thermal reduction-oil bath technology, and oxygen vacancies were introduced to expand the light absorption range, solving the problem of low hydrogen production efficiency of ZnIn2S4-based photocatalysts, and achieving excellent photothermal catalytic decomposition of aquatic hydrogen production performance.

CN119657178APending Publication Date: 2025-03-21RES INST OF XIAN JIAOTONG UNIV & SUZHOU +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411859569.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing ZnIn2S4-based photocatalysts have low hydrogen production efficiency, mainly due to their limited light absorption range, and they cannot effectively utilize the near-infrared light, thus limiting the improvement of photocatalytic performance.

Method used

Through hydrothermal-thermal reduction-oil bath technology, WOx nanorods are synthesized and ZnIn2S4 nanosheets are grown in situ on them to form a one-dimensional/two-dimensional heterojunction structure, and oxygen vacancies are introduced to expand the light absorption range.

Benefits of technology

It significantly improves the light absorption capacity of heterojunctions, optimizes the transmission path of photogenerated carriers, promotes the rapid transmission of interfacial charges, and significantly improves the performance of photothermal catalytic decomposition of aquatic hydrogen.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657178A_ABST
    Figure CN119657178A_ABST
Patent Text Reader

Abstract

The invention discloses a transition metal sulfide heterojunction with wide spectral response as well as a preparation method and application of the transition metal sulfide heterojunction. The transition metal sulfide heterojunction is prepared from the following raw materials: Na2WO4 (1 to 3 mmol), NaCl (2 to 4 mmol), ZnCl2 (0.5 to 1 mmol), InCl3 (1 to 2 mmol), C2H5NS (2 to 4 mmol) and glycerol (8 to 12 mL). The preparation method comprises the following steps: by taking Na2WO4 and NaCl as reactants and water as a solvent, synthesizing a WO3 nanorod by adopting a solvothermal method; the preparation method comprises the following steps: synthesizing WO3 nanorod solid powder, putting the synthesized WO3 nanorod solid powder into a high-temperature reaction furnace filled with argon-hydrogen mixed gas to obtain an oxygen vacancy-containing WO3 (WOx) nanorod, dissolving ZnCl2, InCl3 and C2H5NS into a mixed solvent of water and glycerol, adding the WOx nanorod into the solution, and growing a ZnIn2S4 nanosheet on the surface of the WOx nanorod in situ by using an oil bath method to finally obtain the transition metal sulfide heterojunction. The prepared heterojunction has obvious one-dimensional / two-dimensional structural characteristics, and due to the photo-thermal effect induced by oxygen vacancies and the synergistic effect of providing additional photo-generated charge transfer channels, the prepared transition metal sulfide heterojunction structure shows efficient performance of producing hydrogen by photo-thermal catalytic decomposition of water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalytic nanomaterials, and specifically relates to a transition metal sulfide heterojunction with a wide spectral response, and a preparation method and application thereof. Background Art

[0002] As a clean renewable energy with high energy density, hydrogen energy is considered to be the green energy with the greatest potential to replace fossil fuels in the 21st century. The large-scale conversion of solar energy into clean, efficient and low-cost hydrogen energy through photocatalytic technology can fundamentally solve the problem of clean energy supply for mankind, and the prospects are bright.

[0003] As a core factor affecting the development of photocatalytic technology, efficient photocatalysts have always been a hot topic for photocatalytic researchers. Among many semiconductor photocatalysts, ZnIn2S4 (ZIS) has the advantages of suitable band gap, high reduction potential, simple preparation process and high chemical stability, and has attracted much attention from researchers in recent years. However, due to its low photocarrier separation efficiency and low photoresponse, the photocatalytic efficiency of pure ZIS is not ideal. In recent years, people have optimized the photocatalytic activity of ZIS through various approaches such as structural engineering, ion doping, loading of co-catalysts and heterostructure construction. Among these methods, the construction of heterojunctions is considered to be an effective method because it can accelerate the transport and separation of photocarriers by inducing a built-in electric field at the interface, thereby improving the photocatalytic performance of water decomposition and hydrogen production. Researchers have reported several cleverly designed and synthesized ZnIn2S4-based heterojunction photocatalysts, including FeNi2S4@ZnIn2S4, ZnIn2S 4 / Both CoIn2S4 and TiO2 / ZnIn2S4 show high photocatalytic hydrogen production activity.

[0004] Although great progress has been made in the construction of heterojunctions, the hydrogen production efficiency of ZnIn2S4-based photocatalysts is still far from practical application. This is because the light absorption of heterojunction components prepared by traditional methods is limited. Most of them only absorb ultraviolet (UV) and visible light to generate photogenerated carriers, but cannot capture near-infrared (NIR) light, which accounts for 53% of the solar spectrum energy, thus greatly limiting the further improvement of photocatalytic performance (Reference 1: Nano Energy 95 (2022) 107028). As an n-type semiconductor, WO3 has been widely used in water purification, CO2 reduction, and photocatalytic oxygen production due to its suitable band gap. In addition, the introduction of oxygen vacancies in WO3 can easily extend its light absorption to near-infrared light, realizing the effective utilization of solar light. Oxygen vacancies introduced by traditional methods such as liquid phase reduction and plasma treatment are unstable and have a relatively low concentration, and the overall structure of the material is easily destroyed during the reaction. Therefore, when it is composited with ZnIn2S4 to construct a heterojunction, it cannot improve the light absorption capacity. On the contrary, the catalytic performance is reduced due to the destruction of the material structure, which seriously hinders the improvement of the photocatalytic hydrogen production efficiency. At the same time, the yield prepared by this method is very low and cannot meet the needs of large-scale use (Reference 2: Applied Catalysis B: Environmental 320 (2023) 122013). In short, the current preparation methods of ZnIn2S4-based heterojunction photocatalytic nanomaterials with wide spectral response are limited, which hinders their further application. Professor Zhou Wei of Heilongjiang University reported a Cu with wide spectral response. 2-x -ZnIn2S4 heterojunction photocatalytic nanomaterials prepared by a four-step method 2-x -ZnIn2S4 exhibits excellent light absorption and hydrogen production performance, but the preparation method is complex and time-consuming, which hinders its scale-up (Reference 3: Small 2022,18,2202544). Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a transition metal sulfide heterojunction with a wide spectral response and a preparation method and application thereof, by using the hydrothermal-thermal reduction-oil bath technology, first synthesizing WO3 nanorods, then introducing oxygen vacancies into the WO3 nanorods by thermal reduction, and finally using the oil bath method on the WO x ZnIn2S4 nanosheets are in situ grown on the nanorods, forming a one-dimensional / two-dimensional heterojunction structure with close interface contact. Due to the presence of oxygen vacancies, on the one hand, the light absorption of the heterojunction is significantly improved, resulting in a photothermal effect. On the other hand, the defect energy levels generated optimize the transmission path of photogenerated carriers. The two form a synergistic effect and promote the rapid transmission of charges at the heterojunction interface, thereby obtaining excellent photothermal catalytic water decomposition and hydrogen production performance.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A transition metal sulfide heterojunction with a broad spectral response, the structure of which is WO x In situ growth of ZnIn2S4 nanosheets on nanorods.

[0008] The raw materials of the transition metal sulfide heterojunction include: Na2WO4 (1-3 mmol), NaCl (2-4 mmol), ZnCl2 (0.5-1 mmol), InCl3 (1-2 mmol), C2H5NS (2-4 mmol) and glycerol (8-12 mL).

[0009] A method for preparing a transition metal sulfide heterojunction with a wide spectral response comprises the following steps:

[0010] S1. Dissolve Na2WO4 (1-3 mmol) and NaCl (2-4 mmol) in H2O (60-80 mL) and prepare a WO3 precursor mixture by a solvothermal method;

[0011] S2, centrifuging the WO3 precursor mixture prepared in step S1 at a speed of 6000-8000 r / min for 5-10 min, retaining the lower layer of solid product, and then washing it with deionized water and ethanol at a speed of 6000-8000 r / min for 3-5 times, each time for 5-10 min, to obtain a gray solid product;

[0012] S3, vacuum drying the gray solid product, vacuum degree 0.01-10Pa, temperature 60-80℃, time 8-10h; then grinding into powder, placing it under the condition of circulating argon-hydrogen mixed gas for high temperature reduction to obtain blue-black powder, which is WO x Nanorods;

[0013] S4, dissolve ZnCl2 (0.5-1 mmol), InCl3 (1-2 mmol), C2H5NS (2-4 mmol) in a mixed solution of water and hydrochloric acid (32-48 mL) with a pH of 1.5-2.5 and glycerol (8-12 mL), then add WO x The nanorods were 0.01-0.04 mmol, and then the solution was stirred for 30-60 min to prepare WO by oil bath method. x / ZnIn2S4 heterojunction mixed solution;

[0014] S5, the WO prepared in step S4 x / ZnIn2S4 heterojunction mixed liquid, centrifuge at a speed of 6000-8000r / min for 5-10min, retain the lower layer of solid product, and then use deionized water and ethanol to centrifuge and wash 3-5 times at a speed of 6000-8000r / min, each time for 5-10min, to obtain a dark yellow solid product; the obtained dark yellow solid product is vacuum dried at a vacuum degree of 0.01-10Pa, a temperature of 60-80°C, and a time of 8-10h to obtain a dark yellow powder, which is a transition metal sulfide heterojunction.

[0015] The specific steps of the solvothermal method in step S1 are as follows: dissolving Na2WO4 (1-3mmol) and NaCl (2-4mmol) in H2O (60-80mL), and then adjusting the pH of the solution to 1.5-2.5 with hydrochloric acid, stirring the solution for 20-40min, and finally placing it at a high temperature of 160-200°C for 18-30h, and naturally cooling it to room temperature after the reaction is completed.

[0016] The molar ratio of Na2WO4 to NaCl is 1:1.5-1:3.

[0017] The specific conditions of the high-temperature reduction treatment in step S3 are: heating to 400-600°C at a heating rate of 2-5°C / min, and keeping warm for 1-3h, and naturally cooling to room temperature after the reaction; during the high-temperature reduction treatment, the flow rate of the argon-hydrogen mixture is 100-300sccm, and the volume proportion of hydrogen in the argon-hydrogen mixture is 5-10%.

[0018] The specific conditions of the oil bath method in step S4 are: the oil bath temperature is 70-90° C., the oil bath time is 2-4 hours, and finally the oil bath is naturally cooled to room temperature.

[0019] The molar ratio of ZnCl2, InCl3 and C2H5NS is 1:1:2-1:2:4.

[0020] A transition metal sulfide heterojunction with a wide spectral response is prepared by any of the above preparation methods.

[0021] Based on the application of the above-mentioned transition metal sulfide heterojunction with wide spectral response, the prepared transition metal sulfide heterojunction is used as a photocatalyst in photothermal catalytic decomposition of water to produce hydrogen.

[0022] The beneficial effects of the present invention are:

[0023] (1) Traditional strategies for introducing oxygen vacancies are mostly liquid phase reduction and plasma treatment. The oxygen vacancies obtained are unstable and have a relatively low concentration. In addition, the overall structure of the material is easily destroyed during the reaction, thereby failing to improve the light absorption capacity. The present invention provides a three-step synthesis method. First, a WO3 nanorod structure is synthesized by a hydrothermal method. Then, oxygen vacancies are introduced into WO3 by finely controlling the thermal reduction conditions (reaction temperature, time and other parameters). Finally, an oil bath method is used to synthesize the WO3 nanorod structure. x ZnIn2S4 nanosheets are in situ grown on the nanorods, forming a one-dimensional / two-dimensional heterojunction structure with close interface contact. Compared with the traditional WO3 / ZnIn2S4 heterojunction, oxygen vacancies are innovatively introduced, which significantly improves the photocatalytic performance.

[0024] (2) Traditional strategies for regulating oxygen vacancies, such as sodium borohydride etching and plasma treatment, introduce limited and unstable oxygen vacancies. The present invention provides a method for introducing stable oxygen vacancies with adjustable oxygen vacancy concentration. The introduced oxygen vacancies significantly improve the light absorption of the heterojunction and induce a photothermal effect. At the same time, the presence of defect energy levels optimizes the transmission path of photogenerated carriers and jointly promotes interfacial charge transport, thereby significantly improving the performance of photothermal catalytic water decomposition to produce hydrogen.

[0025] (3) WO was obtained by KM equation and Mott–Schottky test. x The band gap and conduction and valence band positions of ZnIn2S4 form a Z-type band matching structure. x The photogenerated electrons in the conduction band and defect levels recombine with the photogenerated holes in the valence band of ZnIn2S4. The photogenerated electrons in the conduction band of ZnIn2S4 participate in the reduction reaction to generate hydrogen. x The photogenerated holes in the valence band undergo oxidation reaction.

[0026] In summary, the present invention uses the hydrothermal-thermal reduction-oil bath technology to form a one-dimensional / two-dimensional heterojunction structure with close interface contact as a whole; due to the presence of oxygen vacancies, on the one hand, the light absorption of the heterojunction is significantly improved to produce a photothermal effect, and on the other hand, the defect energy levels generated optimize the transmission path of photogenerated carriers. The two form a synergistic effect and promote the rapid transmission of charges at the heterojunction interface, thereby obtaining excellent photothermal catalytic decomposition of water to produce hydrogen performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is the morphology structure and element distribution diagram of the transition metal sulfide heterojunction prepared by the present invention; wherein, Figure 1 a is the SEM image of the heterojunction. Figure 1 b is the TEM image, Figure 1 c- Figure 1h is the element distribution diagram of the heterojunction.

[0028] Figure 2 is a phase structure diagram of the transition metal sulfide heterojunction prepared by the present invention; wherein, Figure 2 a is XRD phase analysis, Figure 2 b is the electron paramagnetic resonance spectrum of the heterojunction.

[0029] Figure 3 This is a performance test diagram of photothermal catalytic decomposition of water to produce hydrogen by the transition metal sulfide heterojunction prepared by the present invention; wherein, Figure 3 a is the graph showing the change of hydrogen production performance over time for all samples. Figure 3 b is the photocatalytic hydrogen production rate diagram of all samples. Figure 3 c is a comparison chart of the hydrogen production performance of the heterojunction synthesized in this work and the reported ZnIn2S4-based heterojunction photocatalyst.

[0030] Figure 4 It is a diagram of the energy band position and photocatalytic reaction mechanism of the transition metal sulfide heterojunction prepared by the present invention. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with the accompanying drawings and embodiments; in order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific implementation methods and with reference to the accompanying drawings. It should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, the description of well-known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0032] Example 1

[0033] This embodiment provides a method for preparing a transition metal sulfide heterojunction with a wide spectral response, comprising the following steps:

[0034] S1. Dissolve 1mmol Na2WO4 and 2mmol NaCl in 80mL H2O, then adjust the pH of the solution to 1.5 with hydrochloric acid, then stir the solution for 40min, finally transfer it to a reactor, place it in a high temperature oven at 200℃ for 30h, and naturally cool it to room temperature after the reaction to prepare a WO3 precursor mixed solution;

[0035] S2, transfer the WO3 precursor mixture prepared in S1 into a centrifuge tube, centrifuge at 8000 r / min for 10 min, retain the solid product at the lower layer, and then wash it with deionized water and ethanol respectively at 8000 r / min for 3 times, 10 min / time, to obtain a gray solid product;

[0036] S3, the gray solid product was transferred to a vacuum oven for vacuum drying (vacuum degree 0.01Pa, temperature 80°C, time 10h), then ground into powder, placed in a corundum magnetic boat, and placed as a whole in a high-temperature tube furnace with argon-hydrogen mixed gas flowing for high-temperature reduction, the argon-hydrogen mixed gas flow rate was 100sccm, the temperature was 400°C, the time was 1h, the heating rate was 5°C / min, and the volume proportion of hydrogen in the argon-hydrogen mixed gas was 5%) to obtain a blue-black powder, namely WO x Nanorods;

[0037] S4, 0.5mmol ZnCl2, 1mmol InCl3, 2mmol C2H5NS, dissolved in 40mL pH = 1.5 water and hydrochloric acid mixed solution and 10mL glycerol, then add 0.01mmol WO x The nanorods were then placed in an oil bath at 80°C for 2 h to prepare WO x / ZnIn2S4 heterojunction mixed solution;

[0038] S5. WO x The / ZnIn2S4 heterojunction mixed liquid was transferred to a centrifuge tube and centrifuged at 8000 r / min for 10 min. The lower layer of solid product was retained and then washed with deionized water and ethanol for 3 times at 8000 r / min, 10 min / time, respectively. The obtained dark yellow solid product was then transferred to a vacuum oven for vacuum drying (vacuum degree 0.01 Pa, temperature 80°C, time 10 h) to obtain a dark yellow powder, which is a transition metal sulfide heterojunction.

[0039] Example 2

[0040] This embodiment provides a method for preparing a transition metal sulfide heterojunction with a wide spectral response, comprising the following steps:

[0041] S1. Dissolve 1mmol Na2WO4 and 3mmol NaCl in 80mL H2O, then adjust the pH of the solution to 2 with hydrochloric acid, then stir the solution for 20min, finally transfer it to a reactor, place it in a high temperature oven at 160℃ for 18h, and naturally cool it to room temperature after the reaction to prepare a WO3 precursor mixed solution;

[0042] S2, transfer the WO3 precursor mixture prepared in S1 into a centrifuge tube, centrifuge at 6000 r / min for 8 min, retain the lower layer of solid product, and then wash it with deionized water and ethanol respectively at 6000 r / min for 4 times, 8 min / time, to obtain a gray solid product;

[0043] S3. The gray solid product was transferred to a vacuum oven for vacuum drying (vacuum degree 1Pa, temperature 70°C, time 8h), then ground, placed in a corundum magnetic boat, and placed as a whole in a high-temperature tube furnace with argon-hydrogen mixed gas flowing for high-temperature reduction (argon-hydrogen mixed gas flow rate during the reaction was 200sccm, temperature 500°C, time 2h, heating rate 2°C / min, and the volume proportion of hydrogen in the argon-hydrogen mixed gas was 5%) to obtain a blue-black powder, namely WO x Nanorods;

[0044] S4. Dissolve 1 mmol ZnCl2, 1 mmol InCl3, and 2 mmol C2H5NS in 32 mL of a mixed solution of water and hydrochloric acid at pH = 2 and 8 mL of glycerol, then add 0.02 mmol WO x The nanorods were then placed in an oil bath at 70°C for 2 h to prepare WO x / ZnIn2S4 heterojunction mixed solution;

[0045] S5. WO x The / ZnIn2S4 heterojunction mixed liquid was transferred to a centrifuge tube and centrifuged at 6000 r / min for 8 min. The lower layer of solid product was retained and then washed with deionized water and ethanol respectively by centrifugation at 6000 r / min for 4 times, 8 min / time. The obtained dark yellow solid product was then transferred to a vacuum oven for vacuum drying (vacuum degree 1 Pa, temperature 70°C, time 8 h) to obtain a dark yellow powder, which is a transition metal sulfide heterojunction.

[0046] Example 3

[0047] This embodiment provides a method for preparing a transition metal sulfide heterojunction with a wide spectral response, comprising the following steps:

[0048] S1. Dissolve 2mmol Na2WO4 and 3mmol NaCl in 80mL H2O, then adjust the pH of the solution to 2.5 with hydrochloric acid, stir the solution for 30min, transfer it to a reactor, place it in a high temperature oven at 160℃ for 24h, and naturally cool it to room temperature after the reaction to prepare a WO3 precursor mixed solution;

[0049] S2, transfer the WO3 precursor mixture prepared in S1 into a centrifuge tube, centrifuge at 7000 r / min for 6 min, retain the lower solid product, and then wash it with deionized water and ethanol respectively at 7000 r / min for 3 times, 6 min / time, to obtain a gray solid product;

[0050] S3. The gray solid product was transferred to a vacuum oven for vacuum drying (vacuum degree 5Pa, temperature 60°C, time 9h), then ground into powder, placed in a corundum magnetic boat, and placed as a whole in a high-temperature tube furnace with argon-hydrogen mixed gas flowing for high-temperature reduction (argon-hydrogen mixed gas flow rate during the reaction was 300sccm, temperature 500°C, time 2h, heating rate 2°C / min, and the volume proportion of hydrogen in the argon-hydrogen mixed gas was 6%) to obtain a blue-black powder, namely WO x Nanorods.

[0051] S4, 0.5mmol ZnCl2, 1mmol InCl3, 4mmol C2H5NS, dissolved in 36mL pH = 2 water and hydrochloric acid mixed solution and 9mL glycerol, then add 0.03mmol WO x The nanorods were then placed in an oil bath at 90°C for 1 h to prepare WO x / ZnIn2S4 heterojunction mixed liquid.

[0052] S5. WO x The / ZnIn2S4 heterojunction mixed liquid was transferred to a centrifuge tube and centrifuged at 7000 r / min for 6 min. The lower layer of solid product was retained and then washed with deionized water and ethanol for 3 times at 6000 r / min, 8 min / time, respectively. The obtained dark yellow solid product was then transferred to a vacuum oven for vacuum drying (vacuum degree 5 Pa, temperature 70°C, time 8 h) to obtain a dark yellow powder, which is a transition metal sulfide heterojunction.

[0053] Example 4

[0054] This embodiment provides a method for preparing a transition metal sulfide heterojunction with a wide spectral response, comprising the following steps:

[0055] S1. Dissolve 2mmol Na2WO4 and 4mmol NaCl in 70mL H2O, then adjust the pH of the solution to 2.5 with hydrochloric acid, then stir the solution for 50min, finally transfer it to a reactor, place it in a high temperature oven at 200℃ for 20h, and naturally cool it to room temperature after the reaction to prepare a WO3 precursor mixed solution;

[0056] S2, transfer the WO3 precursor mixture prepared in S1 into a centrifuge tube, centrifuge at 6000 r / min for 8 min, retain the solid product at the lower layer, and then wash it with deionized water and ethanol respectively at 8000 r / min for 4 times, 10 min / time, to obtain a gray solid product;

[0057] S3. The gray solid product was transferred to a vacuum oven for vacuum drying (vacuum degree 1Pa, temperature 70°C, time 9h), then ground, placed in a corundum magnetic boat, and placed as a whole in a high-temperature tube furnace with argon-hydrogen mixed gas flowing for high-temperature reduction (argon-hydrogen mixed gas flow rate during the reaction was 200sccm, temperature 600°C, time 3h, heating rate 4°C / min, and the volume proportion of hydrogen in the argon-hydrogen mixed gas was 6%) to obtain a blue-black powder, namely WO x Nanorods;

[0058] S4. Dissolve 1mmol ZnCl2, 2mmol InCl3, and 4mmol C2H5NS in 44mL of a mixed solution of water and hydrochloric acid at pH=2.5 and 11mL of glycerol, then add 0.04mmol WO x The nanorods were then placed in an oil bath at 90°C for 3 h to prepare WO x / ZnIn2S4 heterojunction mixed solution;

[0059] S5. WO x The / ZnIn2S4 heterojunction mixed liquid was transferred to a centrifuge tube and centrifuged at 6000 r / min for 6 min to retain the lower layer of solid product, which was then washed three times by centrifugation with deionized water and ethanol respectively. The obtained dark yellow solid product was then transferred to a vacuum oven for vacuum drying (vacuum degree 1 Pa, temperature 60°C, time 10 h) to obtain a dark yellow powder, which was a transition metal sulfide heterojunction.

[0060] Example 5

[0061] This embodiment provides a method for preparing a transition metal sulfide heterojunction with a wide spectral response, comprising the following steps:

[0062] S1. Dissolve 2mmol Na2WO4 and 4mmol NaCl in 60mL H2O and prepare a WO3 precursor mixture by solvothermal method;

[0063] S2, the WO3 precursor mixed solution prepared in S1 was transferred to a centrifuge tube, centrifuged at 7000r / min for 9 minutes, the lower layer of solid product was retained, and then the pH of the solution was adjusted to 2.5 with hydrochloric acid, and then the solution was stirred for 40 minutes, and finally transferred to a reactor, placed in a high-temperature oven at 190°C for 18 hours, and naturally cooled to room temperature after the reaction was completed to prepare a WO3 precursor mixed solution;

[0064] S3. The gray solid product was transferred to a vacuum oven for vacuum drying (vacuum degree 2Pa, temperature 80°C, time 8h), then ground, placed in a corundum magnetic boat, and placed as a whole in a high-temperature tube furnace with a circulating argon-hydrogen mixed gas for high-temperature reduction (the argon-hydrogen mixed gas flow rate during the reaction was 100sccm, the temperature was 600°C, the time was 1h, the heating rate was 5°C / min, and the volume proportion of hydrogen in the argon-hydrogen mixed gas was 7%) to obtain a blue-black powder, namely WO x Nanorods;

[0065] S4, 0.5mmol ZnCl2, 1.5mmol InCl3, 4mmol C2H5NS, dissolved in 48mL pH = 2.5 water and hydrochloric acid mixed solution and 12mL glycerol, then add 0.01mmol WO x The nanorods were then placed in an oil bath at 80 °C for 3 h to prepare WO x / ZnIn2S4 heterojunction mixed solution;

[0066] S5. WO x The ZnIn2S4 heterojunction mixed liquid was transferred to a centrifuge tube and centrifuged at 8000 r / min for 8 min. The solid product in the lower layer was retained and then washed with deionized water and ethanol, respectively, by centrifugation at 8000 r / min for 3 times, 10 min / time. The obtained dark yellow solid product was then transferred to a vacuum oven for vacuum drying (vacuum degree 2 Pa, temperature 70°C, time 8 h) to obtain a dark yellow powder, which is a transition metal sulfide heterojunction.

[0067] Example 6

[0068] This embodiment provides a method for preparing a transition metal sulfide heterojunction with a wide spectral response, comprising the following steps:

[0069] S1. Dissolve 1.5mmol Na2WO4 and 3mmol NaCl in 80mL H2O, then adjust the pH of the solution to 2 with hydrochloric acid, then stir the solution for 20min, finally transfer it to a reactor, place it in a high temperature oven at 160℃ for 18h, and naturally cool it to room temperature after the reaction to prepare a WO3 precursor mixed solution;

[0070] S2, transfer the WO3 precursor mixture prepared in S1 into a centrifuge tube, centrifuge at 8000 r / min for 10 min, retain the lower layer of solid product, and then wash it with deionized water and ethanol at 6000 r / min for 4 times, 8 min / time, to obtain a gray solid product;

[0071] S3. The gray solid product was transferred to a vacuum oven for vacuum drying (vacuum degree 3Pa, temperature 60°C, time 6h), then ground, placed in a corundum magnetic boat, and placed as a whole in a high-temperature tube furnace with argon-hydrogen mixed gas flowing for high-temperature reduction (argon-hydrogen mixed gas flow rate during the reaction was 200sccm, temperature 500°C, time 2h, heating rate 5°C / min, and the volume proportion of hydrogen in the argon-hydrogen mixed gas was 8%) to obtain a blue-black powder, namely WO x Nanorods;

[0072] S4, 0.5mmol ZnCl2, 1.5mmol InCl3, 4mmol C2H5NS, dissolved in 40mL pH = 2.5 water and hydrochloric acid mixed solution and 10mL glycerol, then add 0.02mmol WO x The nanorods were then placed in an oil bath at 80 °C for 3 h to prepare WO x / ZnIn2S4 heterojunction mixed solution;

[0073] S5. WO x The / ZnIn2S4 heterojunction mixed liquid was transferred to a centrifuge tube and centrifuged at 6000 r / min for 6 min to retain the lower layer of solid product. It was then washed with deionized water and ethanol for 5 times at 6000 r / min, 8 min / time, respectively. The obtained dark yellow solid product was then transferred to a vacuum oven for vacuum drying (vacuum degree 3 Pa, temperature 80°C, time 9 h) to obtain a dark yellow powder, which is a transition metal sulfide heterojunction.

[0074] Example 7

[0075] This embodiment provides a method for preparing a transition metal sulfide heterojunction with a wide spectral response, comprising the following steps:

[0076] S1. Dissolve 1.5mmol Na2WO4 and 2mmol NaCl in 70mL H2O, then adjust the pH of the solution to 2 with hydrochloric acid, then stir the solution for 40min, finally transfer it to a reactor, place it in a high temperature oven at 180℃ for 24h, and naturally cool it to room temperature after the reaction to prepare a WO3 precursor mixed solution;

[0077] S2, transfer the WO3 precursor mixture prepared in S1 into a centrifuge tube, centrifuge at 7000r / min for 10min, retain the lower layer of solid product, and then centrifuge and wash with deionized water and ethanol for 3 times respectively to obtain a gray solid product;

[0078] S3. The gray solid product was transferred to a vacuum oven for vacuum drying (vacuum degree 0.1 Pa, temperature 70°C, time 10 h), then ground, placed in a corundum magnetic boat, and placed as a whole in a high-temperature tube furnace with argon-hydrogen mixed gas flowing for high-temperature reduction (argon-hydrogen mixed gas flow rate during the reaction was 200 sccm, temperature 500°C, time 2 h, heating rate 5°C / min, and the volume proportion of hydrogen in the argon-hydrogen mixed gas was 9%) to obtain a blue-black powder, namely WO x Nanorods;

[0079] S4, 1.5mmol ZnCl2, 1.5mmol InCl3, 4mmol C2H5NS, dissolved in 40mL pH = 2 water and hydrochloric acid mixed solution and 10mL glycerol, then add 0.03mmol WO x The nanorods were then placed in an oil bath at 70°C for 2 h to prepare WO x / ZnIn2S4 heterojunction mixed solution;

[0080] S5. WO x The / ZnIn2S4 heterojunction mixed liquid was transferred to a centrifuge tube and centrifuged at 6000 r / min for 6 min to retain the lower layer of solid product. It was then washed with deionized water and ethanol for 4 times at 6000 r / min, 8 min / time, respectively. The obtained dark yellow solid product was then transferred to a vacuum oven for vacuum drying (vacuum degree 0.1 Pa, temperature 80°C, time 10 h) to obtain a dark yellow powder, which is a transition metal sulfide heterojunction.

[0081] Example 8

[0082] This embodiment provides a method for preparing a transition metal sulfide heterojunction with a wide spectral response, comprising the following steps:

[0083] S1. Dissolve 1.5mmol Na2WO4 and 4mmol NaCl in 80mL H2O, then adjust the pH of the solution to 1.5 with hydrochloric acid, then stir the solution for 60min, finally transfer it to a reactor, place it in a high temperature oven at 200℃ for 24h, and naturally cool it to room temperature after the reaction to prepare a WO3 precursor mixed solution;

[0084] S2, transfer the WO3 precursor mixture prepared in S1 into a centrifuge tube, centrifuge at 6000r / min for 8min, retain the lower solid product, and then wash it with deionized water and ethanol respectively at 7000r / min for 3 times, 6min / time, to obtain a gray solid product;

[0085] S3. The gray solid product was transferred to a vacuum oven for vacuum drying (vacuum degree 1Pa, temperature 80°C, time 9h), then ground, placed in a corundum magnetic boat, and placed in a high-temperature tube furnace with argon-hydrogen mixed gas for high-temperature reduction (argon-hydrogen mixed gas flow rate of 300sccm, temperature 500°C, time 3h, heating rate 2°C / min, hydrogen volume proportion of argon-hydrogen mixed gas was 10%) to obtain a blue-black powder, namely WO x Nanorods.

[0086] S4. Dissolve 1 mmol ZnCl2, 1.5 mmol InCl3, and 3 mmol C2H5NS in 48 mL of a mixed solution of water and hydrochloric acid at pH = 1.5 and 12 mL of glycerol, then add 0.04 mmol WO x The nanorods were then placed in an oil bath at 80°C for 1 h to prepare WO x / ZnIn2S4 heterojunction mixed solution.

[0087] S5. WO x The / ZnIn2S4 heterojunction mixed liquid was transferred to a centrifuge tube and centrifuged at 8000 r / min for 8 min. The lower layer of solid product was retained and then washed with deionized water and ethanol respectively by centrifugation at 6000 r / min for 4 times, 8 min / time. The obtained dark yellow solid product was then transferred to a vacuum oven for vacuum drying (vacuum degree 1 Pa, temperature 80°C, time 8 h) to obtain a dark yellow powder, which is a transition metal sulfide heterojunction.

[0088] The ratio of the volume of the solvent in the reactor of the present invention to the total volume of the inner lining of the reactor is 1:2-3:4.

[0089] The morphology and structure of the transition metal sulfide heterojunction prepared in Example 1 of the present invention are as follows: Figure 1 As shown: Figure 1 a and 1b are the SEM and TEM images of the prepared tantalum oxynitride, respectively. ZnIn2S4 nanosheets are closely grown on WO x The nanorod surface provides a fast channel for the migration of photogenerated carriers at the interface. TEM images also show this close heterogeneous interface. Figure 1 c-1h is the element distribution mapping of the tantalum oxide, showing the uniform distribution of Zn, In, S, W and O elements.

[0090] The phase structure of the transition metal sulfide heterojunction prepared in Example 1 of the present invention is as follows: Figure 2 As shown: Figure 2a is the XRD phase analysis, the main diffraction peak of ZnIn2S4 is attributed to the hexagonal phase ZnIn2S4 ((JCPDS#72-0773). x / ZnIn2S4 composite materials, all diffraction peaks come from ZnIn2S4 and WO x With the typical peak of WO x With the increase of content, the diffraction peak intensity of ZIS weakens, while that of WO x On the contrary, it indicates the successful construction of the heterojunction. Figure 2 As shown in b, WO x The EPR spectrum of / ZnIn2S4 has an enhanced signal at g=2.003, indicating the existence of oxygen vacancies in the composite material.

[0091] The photothermal catalytic decomposition of water to produce hydrogen by the transition metal sulfide heterojunction prepared in Example 1 of the present invention is tested as follows: Figure 3 shown. Figure 3 a shows the variation of hydrogen production of all prepared samples with illumination time. It can be seen that the hydrogen production of most samples increases with the increase of illumination time, except for WO3, which has no photocatalytic activity. Figure 3 b shows the photocatalytic hydrogen production rates of all samples. ZnIn2S4 exhibits poor photocatalytic hydrogen production performance of 34.13 μmol h due to the rapid recombination of photogenerated carriers. -1 The use of WO3 to construct a heterojunction improves the photocatalytic activity, and the introduction of oxygen vacancies further improves the photocatalytic activity. x Insufficient or excessive addition will lead to a decrease in the hydrogen evolution rate. This is because ZnIn2S4 cannot be completely wrapped in WO x The surface or ZnIn2S4 is excessively aggregated, thus reducing the separation efficiency of photogenerated carriers. x The photocatalytic activity of ZnIn2S4 is 339.07 μmol h -1 , which is 9.4 times the photocatalytic activity of pure ZnIn2S4. Figure 3 c shows the WO prepared by the present invention x The activity comparison of WO / ZnIn2S4 heterojunction photocatalyst and other reported ZnIn2S4-based photocatalysts shows that the WO / ZnIn2S4 heterojunction photocatalyst prepared by the method of the present invention can be x The photocatalytic performance of the / ZnIn2S4 heterojunction photocatalyst is significantly higher than that reported elsewhere, demonstrating the superiority of the preparation method of the present invention.

[0092] The energy band position and charge transfer mechanism of the transition metal sulfide heterojunction prepared by the present invention are as follows: Figure 4Taking the transition metal sulfide heterojunction prepared in Example 1 as an example, it can be seen that the KM equation and Mott–Schottky test results show that the band gaps of ZnIn2S4 and WO3 are 2.86eV and 3.19eV respectively, and the two form a Z-type energy band matching structure. x The photogenerated electrons in the conduction band and defect levels recombine with the photogenerated holes in the valence band of ZnIn2S4. The photogenerated electrons in the conduction band of ZnIn2S4 participate in the reduction reaction to generate hydrogen. x The photogenerated holes in the valence band undergo oxidation reaction.

[0093] In summary, the present invention provides a transition metal sulfide heterojunction with a wide spectral response, a preparation method and an application thereof, and also provides an application thereof in photothermal catalytic decomposition of water to produce hydrogen. The present invention first synthesizes WO3 nanorods by a hydrothermal-thermal reduction-oil bath technique, then introduces oxygen vacancies into the WO3 nanorods by a thermal reduction method, and finally forms a WO3 nanorod in an oil bath method. x ZnIn2S4 nanosheets are in situ grown on the nanorods, forming a one-dimensional / two-dimensional heterojunction structure with close interface contact. Due to the presence of oxygen vacancies, on the one hand, the light absorption of the heterojunction is significantly improved, resulting in a photothermal effect, and on the other hand, the defect energy levels generated optimize the transmission path of the photogenerated carriers. The two form a synergistic effect and promote the rapid transmission of charges at the heterojunction interface, thereby obtaining excellent photothermal catalytic decomposition of water to produce hydrogen, showing good practical potential.

[0094] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the appended claims of the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the appended claims or the equivalent forms of such scope and boundaries.

Claims

1. A transition metal sulfide heterojunction with a wide spectral response, characterized in that: Its structure is WO x In situ growth of ZnIn2S4 nanosheets on nanorods.

2. A transition metal sulfide heterojunction with a wide spectral response according to claim 1, characterized in that: The raw materials of the transition metal sulfide heterojunction include: Na2WO4 (1-3 mmol), NaCl (2-4 mmol), ZnCl2 (0.5-1 mmol), InCl3 (1-2 mmol), C2H5NS (2-4 mmol) and glycerol (8-12 mL).

3. A method for preparing a transition metal sulfide heterojunction with a wide spectral response, characterized in that: The specific steps include: S1. Dissolve Na2WO4 (1-3 mmol) and NaCl (2-4 mmol) in H2O (60-80 mL) and prepare a WO3 precursor mixture by a solvothermal method; S2, centrifuging the WO3 precursor mixture prepared in step S1 at a speed of 6000-8000 r / min for 5-10 min, retaining the lower layer of solid product, and then washing it with deionized water and ethanol at a speed of 6000-8000 r / min for 3-5 times, each time for 5-10 min, to obtain a gray solid product; S3, vacuum drying the gray solid product, vacuum degree 0.01-10Pa, temperature 60-80℃, time 8-10h; then grinding into powder, placing it under the condition of circulating argon-hydrogen mixed gas for high temperature reduction to obtain blue-black powder, which is WO x Nanorods; S4, dissolve ZnCl2 (0.5-1 mmol), InCl3 (1-2 mmol), C2H5NS (2-4 mmol) in a mixed solution of water and hydrochloric acid (32-48 mL) with a pH of 1.5-2.5 and glycerol (8-12 mL), then add WO x The nanorods were 0.01-0.04 mmol, and then the solution was stirred for 30-60 min to prepare WO by oil bath method. x / ZnIn2S4 heterojunction mixed solution; S5, the WO prepared in step S4 x / ZnIn2S4 heterojunction mixed liquid, centrifuge at a speed of 6000-8000r / min for 5-10min, retain the lower layer of solid product, and then use deionized water and ethanol to centrifuge and wash 3-5 times at a speed of 6000-8000r / min, each time for 5-10min, to obtain a dark yellow solid product; the obtained dark yellow solid product is vacuum dried at a vacuum degree of 0.01-10Pa, a temperature of 60-80°C, and a time of 8-10h to obtain a dark yellow powder, which is a transition metal sulfide heterojunction.

4. The method for preparing a transition metal sulfide heterojunction with a wide spectral response according to claim 3, characterized in that: The specific steps of the solvothermal method in step S1 are as follows: dissolving Na2WO4 (1-3mmol) and NaCl (2-4mmol) in H2O (60-80mL), and then adjusting the pH of the solution to 1.5-2.5 with hydrochloric acid, stirring the solution for 20-40min, and finally placing it at a high temperature of 160-200°C for 18-30h, and naturally cooling it to room temperature after the reaction is completed.

5. The method for preparing a transition metal sulfide heterojunction with a wide spectral response according to claim 3, characterized in that: The molar ratio of Na2WO4 to NaCl is 1:1.5-1:

3.

6. The method for preparing a transition metal sulfide heterojunction with a wide spectral response according to claim 3, characterized in that: The specific conditions of the high-temperature reduction treatment in step S3 are: heating to 400-600°C at a heating rate of 2-5°C / min, and keeping warm for 1-3h, and naturally cooling to room temperature after the reaction; during the high-temperature reduction treatment, the flow rate of the argon-hydrogen mixture is 100-300sccm, and the volume proportion of hydrogen in the argon-hydrogen mixture is 5-10%.

7. The method for preparing a transition metal sulfide heterojunction with a wide spectral response according to claim 3, characterized in that: The specific conditions of the oil bath method in step S4 are: the oil bath temperature is 70-90° C., the oil bath time is 2-4 hours, and finally the oil bath is naturally cooled to room temperature.

8. The method for preparing a transition metal sulfide heterojunction with a wide spectral response according to claim 3, characterized in that: The molar ratio of ZnCl2, InCl3 and C2H5NS is 1:1:2-1:2:

4.

9. A transition metal sulfide heterojunction with a broad spectral response, characterized in that: Prepared by the method described in any one of claims 3 to 8.

10. The application of the transition metal sulfide heterojunction with wide spectral response according to any one of claims 1 to 9, characterized in that: The prepared transition metal sulfide heterojunction is used as a photocatalyst in photothermal catalytic decomposition of water to produce hydrogen.

Citation Information

Cited By

  • Wide-spectrum ZnIn2S4 / WO3 quantum dot composite photocatalyst as well as preparation method and application thereof

    CN120861096A